2013
DOI: 10.1186/1742-2094-10-126
|View full text |Cite
|
Sign up to set email alerts
|

Glatiramer acetate treatment effects on gene expression in monocytes of multiple sclerosis patients

Abstract: BackgroundGlatiramer acetate (GA) is a mixture of synthetic peptides used in the treatment of patients with relapsing-remitting multiple sclerosis (RRMS). The aim of this study was to investigate the effects of GA therapy on the gene expression of monocytes.MethodsMonocytes were isolated from the peripheral blood of eight RRMS patients. The blood was obtained longitudinally before the start of GA therapy as well as after one day, one week, one month and two months. Gene expression was measured at the mRNA leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 84 publications
0
10
0
Order By: Relevance
“…60 Direct association in the literature between macrophages and the underexpressed gene Ptprcap was less clear, although it has been found in the monocyte precursors to macrophages. 61 However, Ptprcap is known as a CD45-associate, regulating the interaction of CD45 with other proteins. As CD45 regulates apoptosis, this may explain the relationship to immune-challenge.…”
Section: Discussionmentioning
confidence: 99%
“…60 Direct association in the literature between macrophages and the underexpressed gene Ptprcap was less clear, although it has been found in the monocyte precursors to macrophages. 61 However, Ptprcap is known as a CD45-associate, regulating the interaction of CD45 with other proteins. As CD45 regulates apoptosis, this may explain the relationship to immune-challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Glatiramer Acetate (GA; copolymer 1), a mixture of synthetic peptides mimicking myelin basic protein, used as a first-line treatment option for RR-MS, inhibits a tryptophanyl-tRNA synthetase known to modulate angiogenic signalling [206,207]. The selective adhesion molecule inhibitor Natalizumab, which binds integrin-α4 on endothelial cells and blocks the VCAM-1 driven transmigration of immune cells sensitized against myelin antigen from the vessel lumen to the neuropil across the BBB, precludes VEGF-induced angiogenesis [208,209].…”
Section: Therapeutic Potential Of Targeting Angiogenesismentioning
confidence: 99%
“…In a stroke model, exogenous VEGF administration increases neurogenesis of the SVZ, only after 28 days, without concomitant angiogenesis, demonstrating that a specific VEGF isoform could protect neurons independently of the endothelial cell influence [231]. In the EAE model, despite several reports of an improved clinical score after early VEGF inhibition, one study [232] demonstrated that pertussis toxin stimulated VEGF expression and that VEGF neuroprotection could Fingolimod Gilenya [210][211][212] Glatiramer acetate Copaxone [206,207] Interferon β-1a Avonex, Rebif [84,204,205] Interferon β-1b Betaferon, Extavia Mitoxantrone Novantrone [216] Natalizumab Tysabri [208,209] Teriflunomide Aubagio Only indirect evidence derived from antilymphocytes activity be responsible for milder disease. VEGF may have different effects in different cell types depending on different splice variants [233].…”
Section: Therapeutic Potential Of Targeting Angiogenesismentioning
confidence: 99%
“…APLs do not need to displace all of the antigens in order to function: they need only occupy sufficient MHC receptors that their anti‐inflammatory response balances the pro‐inflammatory response elicited from the antigen . However, no traditional APL has reached the clinic although there are a number of candidates, such as glatiramer triacetate, that may have some APL activity in addition to other mechanisms of action. HLABs on the other hand rely on near complete displacement of the natural antigen.…”
Section: Introductionmentioning
confidence: 99%